(untitled) (JED (Jurnal Etika Demokrasi), 2020)
This Research is aimed at describing the management of inclusive schools which can be used as a reference for principals, teachers and stakeholders in the management of inclusive school environments. This article is the result of a qualitative descriptive study conducted at SDN 33 Payakumbuh. The informants of this study were the school principal, class teacher, special assistant teacher (GPK) and students. Collection techniques use observation, interviews and documentation. Data were analyzed through three pairs namely data reduction, data presentation, and concluding. The results showed that the inclusion of Environmental Management in SDN 33 Payakumbuh was carried out in two aspects, namely physical accessibility and fostering a conducive environment. Both aspects have not been fulfilled optimally by the school. In terms of physical accessibility, it still requires facilities and infrastructure that do not meet the service standards of Children with Special Needs. The results also show facts about the synergy and cooperation of parties ranging from school principals, teachers, administrative staff, students and parents to foster a conducive inclusive school environment. Keywords: Management, Environment, Elementary School, Inclusion Artikel ini, bertujuan untuk mendeskripsikan manajemen lingkungan sekolah inklusi yang dapat dijadikan salah satu rujukan kepala sekolah, guru dan stakeholder dalam mengelolaan lingkungan sekolah inklusif. Artikel ini merupakan hasil penelitian deskriptif kualitatif yang dilaksanakan di SDN 33 Payakumbuh. Informan dalam penelitian ini adalah Kepala sekolah, Guru kelas, Guru pendamping Khusus (GPK) dan siswa. Tehnik pengumpulan menggunakan observasi, wawancara dan dokumentasi. Data dianalisis melalui tiga tahap yaitu reduksi data, penyajian data, dan menarik kesimpulan. Hasil penelitian menunjukkan bahwa Manajemen lingkungan sekolah inklusi di SDN 33 Payakumbuh dilaksanakan dalam dua aspek yakni aksessbilitas fisik dan menumbuhkan iklim yang kondusif. Kedua aspek ini belum terpenuhi oleh sekolah secara optimal. Ditinjau dari aksebilitas fisik masih terdapat sarana dan prasarana yang tidak memenuhi standar pelayanan Anak Berkebutuhan Khusus. Hasil penelitian juga menunjukkan bahwa terdapat sinergi dan kerjasama berbagai pihak mulai dari kepala sekolah, guru, staf administrasi, siswa dan orang tua untuk menumbuhkan lingkungan sekolah inklusif yang kondusif. Kata Kunci: Manajemen, Lingkungan, Sekolah Dasar, Inklusi